SIMULATION TECHNOLOGIES AND OSCE METHODOLOGY IN TEACHING CLINICAL SKILLS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Simulation-based teaching (SBT) has become a key approach in medical education, enhancing students’ clinical competence and learning experience. It includes methods such as high-fidelity mannequins, virtual reality, standardized patients, and hybrid simulations, providing a safe environment to practice both technical and non-technical skills, ultimately improving patient safety.